Hochschild and cyclic homology of Yang–Mills algebras - Herscovich Ramoneda, Estanislao Benito (2012)
The aim of this article is to present a detailed algebraic computation of the Hochschild and cyclic homology groups of the Yang–Mills algebras YM(n) (n ∈ ℕ≧2) defined by A. Connes and M. Dubois-Violette in [8], continuing thus the study of these algebras that we have initiated in [17]. The computation involves the use of a spectral sequence associated to the natural filtration on the universal enveloping algebra YM(n) provided by a Lie ideal (n) in (n) which is free as Lie algebra. As a corollary, we describe the Lie structure of the first Hochschild cohomology group.